Influence of El Niño and La Niña on coffee yield in the main coffee-producing regions of Brazil - Almeida Silva, Karita [UNESP]; de Souza Rolim, Glauco [UNESP]; Borges Valeriano, Taynara Tuany [UNESP]; da Silva Cabral de Moraes, José Reinaldo [UNESP] (Springer Nature, 2020)
Coffee is the most consumed beverage and one of the most valuable commodities worldwide. The crop is very sensitive to meteorological elements, mainly at the microclimatic scale, such as solar radiation, air temperature, and precipitation. El Niño and La Niña are atmospheric phenomena characterized by temperature anomalies in tropical areas of the Pacific Ocean, and changing wind and precipitation patterns in tropical and mid-latitude regions. For these reasons, the objective of this study was to evaluate the influence of El Niño and La Niña on Coffea arabica and canephora yields in the states and localities of the main Brazilian coffee-producing regions. We considered the states of Minas Gerais, São Paulo, Paraná, Bahia, Espírito Santo, and Rondônia. The yield data were obtained from 79 localities for the period 2002–2017 from the Brazilian Institute of Geography. Daily mean air temperature and precipitation were obtained from the NASA-POWER platform and the quarterly registry of the value of the ONI index was obtained from the National Oceanic and Atmospheric Administration. El Niño tended to decrease precipitation, and increase temperature and water deficits for all Brazilian coffee regions. Neutral and La Niña years were climatically similar. Climatic elements tended to be less variable and favor high coffee yields during El Niño years at national, regional, and local scales. The yield increase occurred because the hottest days of EN happen in the first quarter of the phenological cycle, when the crop is normally in the vegetative phase, favoring the generation of new branches. The highest historical yields were generally correlated with the occurrence of El Niño.
Keywords: Applied climatology; Climate change; Coffea sp; ENSO